Analisis Kepatuhan Wajib Pajak Kendaraan Bermotor pada SAMSAT Binjai - Putri, Azra Naisya; Junawan, Junawan (JURNAL RISET RUMPUN ILMU PENDIDIKAN, 2026)
This study analyzes motor vehicle tax (PKB) compliance at the Binjai SAMSAT Office (2020–2024) using a quantitative descriptive approach. Significant fluctuations were detected: a drastic decrease in 2023 (83.98%) and a sharp increase in 2024 (167.91%). Service quality and taxpayer awareness have a positive effect on compliance. However, the tax amnesty policy and the effectiveness of fines have complex impacts and are strongly suspected of causing late payments and reducing the deterrent effect. The decrease in compliance in 2023 is thought to be related to the tax amnesty policy, which reduces incentives to pay on time. Conversely, the surge in compliance in 2024 can be explained as a response to improved services and a more intensive tax awareness campaign. While tax amnesty may help increase revenue in the short term, this study highlights the importance of consistent enforcement of sanctions to maintain long-term payment discipline. Recommendations include improving services, improving tax education, and evaluating fines and the tax amnesty policy. This research also emphasizes the need for a deeper understanding of the impact of amnesty policies on tax compliance patterns, as well as the crucial role of public awareness in increasing compliance with tax obligations. By utilizing empirical data, this study provides valuable insights for future tax policy improvements.